A Retrospective Chart Review of Transfusion Practices in the Palliative Care Unit Setting. (March 2019) - Sirianni, Giovanna; Perri, Giulia; Callum, Jeannie; Gardner, Sandra; Berall, Anna; Selby, Debbie
Background: There remains limited data in the literature on the frequency, clinical utility and effectiveness of transfusions in palliative care, with no randomized controlled trials or clinical practice guidelines on this topic. There are no routinely accepted practices in place for the appropriate transfusion of blood products in this setting. Aim: The aim of this study was to retrospectively review all transfusions in the palliative care units of 2, tertiary care hospitals in Canada. The goals were to elucidate the frequency, indications, patient characteristics, and practices around this intervention. Design: Descriptive, retrospective chart review. Setting/Participants: The clinical charts of patients admitted to the palliative care unit and who obtained blood transfusions for the period of April 1, 2015, to March 31, 2017, were reviewed. All patients admitted who obtained a transfusion were included. There were no exclusion criteria. Results: Transfusions in the palliative care units were rare despite their availability (0.9% at Sunnybrook and 1.4% Baycrest) and were primarily given to patients with cancer. The main symptom issues identified for transfusion were fatigue and dyspnea. The majority of patients endorsed symptomatic benefit with minimal adverse reactions though pre- and post-transfusion assessment practices varied greatly between institutions. Conclusions: Transfusions in the palliative care units were infrequent, symptom targeted, and well tolerated, though the lack of standardized pre/post assessment tools limits any ability to draw conclusions about utility. Patients would benefit from additional research in this area and the development of clinical practice guidelines for transfusions in palliative care.